Levels of salivary thiocyanate and its relation with occurrence of micronuclei using exfoliative cytology in smokers and nonsmokers - Prachi Shrigopal Baldawa; Venkatesh V Kulkarni; Ajit V Koshy; Sabeer S Shaikh; Rucha Varu; Garima Srivastava (Wolters Kluwer Medknow Publications, 2016)
Aims: To evaluate the levels of salivary thiocyanate and its relation with the occurrence of micronuclei (MN) using exfoliative cytology in smokers and nonsmokers. Materials and Methods: One hundred and twenty patients were divided into 3 groups: nonsmoker group 1 (control), smokers group 2, and smokers group 3. Their saliva was collected and analyzed for thiocyanate levels, and exfoliative cytology was evaluated for the presence of MN. Statistical Analysis Used: Fisher's exact test and ANOVA test were used. Results: It was seen that as the grade of smoking increased, the levels of salivary thiocyanate and occurrence of MN increased. Conclusions: Detection and quantification of "biomarkers" such as salivary thiocyanate and MN in noninvasive and painless procedures such as oral exfoliative cytology can be an upcoming research domain in the field of cancer prevention and therapeutics.